Temporal dynamics of the deep-sea pink urchin Strongylocentrotus fragilis on the Northeast Pacific continental margin. (March 2023) - Command, Rylan J.; De Leo, Fabio C.; Robert, Katleen
Abstract: The Northeast Pacific continental margin is characterized by strong seasonal upwelling, which drives high primary productivity, and supports high diversity and biomass of benthic megafauna. The recent occurrence of a marine heat wave ("The Blob", sensu Kintisch, 2015) in 2013–2016 resulted in changes to phytoplankton community composition and loss of coastal kelp abundance and diversity, reducing gross primary productivity in the region. However, cumulative effects of marine heat waves and ongoing basin-scale deoxygenation in deep-sea ecosystems remain poorly understood. Here, we use a 7-year time series of physicochemical and video imagery data from Ocean Networks Canada's NEPTUNE observatory to investigate temporal dynamics of the deep-sea pink urchin Strongylocentrotus fragilis in relation to multi-year environmental variability. Using generalized additive models, we show that local S. fragilis density at Barkley Upper Slope (420 m) fluctuated over time and was partially explained by changes in dissolved oxygen concentration and suspended particulate matter in the benthic boundary layer (ADCP backscatter), with high urchin density corresponding to high oxygen and low backscatter. Seafloor dissolved oxygen ranged from 0.80 to 1.89 mL/L and varied seasonally, exhibiting a clear negative correlation with sea surface primary productivity (MODIS satellite Chl-a data), corresponding with the onset of yearly upwelling conditions. However, during the anomalously warm years affected by 'The Blob', dampened upwelling maintained higher dissolved oxygen conditions near the seafloor. S. fragilis density declined during 'Blob' conditions, likely in response to reduced kelp and phytodetritus subsidies from coastal waters. We propose a foraging-respiration trade-off hypothesis, whereby S. fragilis forages in deeper water during weak upwelling and migrates to shallower habitats during low oxygen conditions. S. fragilis is an important bioturbator and detritivore; changes in the density and distribution of this species may directly affect sediment turnover rates and nutrient cycling on the continental margin, with consequences for surface and coastal productivity. https://github.com/rjcommand/ . Highlights: 7 years of video imagery and oceanographic data and with 14 years of trawl surveys. Pink urchin densities mainly controlled by oxygen and availability of phytodetritus. S. fragilis densities were reduced during the blob when detritus subsidies declined. Shoaling of S. fragilis on the shelf may affect other seafloor nutrient cycling.